Bioaccumulation of Cadmium in Nicotiana tabacum L. (Tobacco) Characterized by Soil Properties: A Case Study in the Sichuan Basin, China. (1st October 2021) - Lu, Xu; Zhang, Dan; Ugurlu, Aysenur; Chen, Yulan; Proshad, Ram
Abstract: The objective of this study was to determine the distribution of cadmium (Cd) accumulation in tobacco and identify the relationship between soil properties and plant Cd concentration. Forty soil and tobacco samples were collected from the Sichuan Basin, China (Panzhihua, Luzhou, Guangyuan and Yibin). The results showed the highest Cd in soil (2.94 mg kg −1 ) was in Yibin. Correspondingly, Cd concentrations in tobacco from Yibin were significantly higher than those from the other regions. The Cd concentrations in tobacco from Yibin, Luzhou, Guangyuan and Panzhihua were from 2.22 to 13.14, 0.59 to 2.12, 0.26 to 0.61, 0.10 to 0.37 mg kg −1, respectively. The Cd concentrations in leaves were higher than those in stems and roots. The highest Cd concentrations were in lower leaves, between 0.36 and 13.14 mg kg −1 . In Yibin, the Cd in lower leaves nearly exceeded 10 mg kg −1 and the ratio of the Cd tobacco and soil concentrations (the bioconcentration factor, BCF) was 9.41. Path analysis showed soil pH and cation exchange capacity (CEC) were the most significant properties exhibiting direct effects on Cd accumulation. Stepwise multiple linear regression showed that soil Cd, pH, CEC and organic carbon (OC) were the major factors controlling Cd bioavailability to tobacco leaves, explaining more than 94.0% of the variance. The results are useful in predicting the transfer of Cd from soil to tobacco.